Pengaruh Efikasi Diri Terhadap Hasil Belajar Matematika Siswa Kelas X SMAN Di Jakarta Barat - Baduri, Jayanti; Nurrahmah, Arfatin (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
The purpose of this research to know the effect of self-efficacy toward mathematic achievement. The research was carried out in April 2024 with sample as many as 70 students which was determined by using simple random sampling technique. Data was obtained through student mathematics learning outcome test instruments and self-efficacy questionnaire instruments. The instrument has been tested for validity and reliability so obtained is valid and reliable. Testing requirements analysis using a normality test with Lilliefors retrieved that students learn math results and self-efficacy Gaussian. After the data Gaussian regression linearity test and do significance of regression obtained that the results of learning math students and self-efficacy of significant regression and linear regression. Based on data calculation of the research results, a significance value result is 0.005 (Sig. < 0.05) which means ????0 rejected, so that the results of this research it can be concluded that there is a relation of self-efficacy with the results of learning math students. The determination coefficient (R-Square) obtained 0,108 and Y ̂= 43,543 + 0,306 X it means self-efficacy give influence on the result of learning math students amounted 11%. But there are other factors that contribute to student learning math results amounted to 89%. Keywords: Self-Efficacy, Mathematics Learning Outcomes